A theory of reservation-dwelling American Indian alcohol use risk. [article]. - Spillane, Nichea S.
The authors present a theory for understanding risk for problem drinking among reservation-dwelling American Indians. The theory offers an overall framework for understanding the risk process for this group. It considers the distinction between factors that influence mean levels of American Indian problem drinking and factors that influence individual differences in American Indian drinking. It proposes important contextual differences between reservation-dwelling American Indians and Caucasians that may help explain the higher mean levels of American Indian problem drinking. The theory further holds that, within the high mean level of problem drinking characteristic of many American Indian reservations, individual differences in problem drinking can be explained by very similar personality and learning factors as those that influence problem-drinking levels for other ethnic groups. -- (from the author)